Pengaruh Kualitas Pelayanan Publik Terhadap Kepatuhan Wajib Pajak Di Kantor Pelayanan Pajak Pratama Medan Timur - Gea, Yuni Karlina; Sihombing, Natalia E.; Degodona, Primawati (Research and Community Service UNIVERSITAS KALBIS, 2025)
This research aims to determine the effect of public service quality on individual taxpayer compliance at the East Medan Pratama Tax Service Office. The type of research used in this research is a quantitative approach and uses non-probability sampling to collect samples and produce 100 samples of WPOP SPT Reports. Multiple linear regression analysis is used as a data collection technique and uses the help of the IBM Statistics SPSS 25 application. Based on the results of the research, all independent variables in this research simultaneously influence WPOP compliance. However, partially only the reliability and responsiveness variables influence WPOP compliance at KPP Pratama Medan Timur.